Haiti : Eighth Review Under the Extended Credit Facility and Request for Waiver of Nonobservance of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2015)
EXECUTIVE SUMMARY This is the final review under the Extended Credit Facility (ECF) arrangement. The program contributed to maintaining macroeconomic stability, and there was progress on structural reforms. The authorities intend to request a successor arrangement under the ECF. A new finance minister was appointed in April; uncertainly remains on the timing of elections. Preliminary data suggest that GDP in FY2014 grew by 3.5-4 percent, while inflation increased slightly to about 5 percent. An increase in fuel prices (in October) should result in fiscal savings of at least 1 percent of GDP during FY2015. The March performance criterion on net international reserves (NIR) was met, but although the deficit was lower than projected, the performance criterion on net central bank credit to the central government was missed. Downside risks are significant and include a pull-back of Venezuela-related flows, a resumption of political tensions, and vulnerability to weather events. A total of SDR 1.638 million will become available upon completion of this review, bringing total disbursements under the ECF to SDR 40.950 million. Key Policy Recommendations: -- The policy mix, in particular the adjustment going forward, should come from a lower fiscal deficit rather than from a tighter monetary policy. The FY2015 fiscal deficit should be reduced to mitigate financing risks as part of a medium-term plan to restore fiscal sustainability. -- The central bank should let the exchange rate adjust more to market pressures. Intervention should be parsimonious, geared at avoiding excess volatility and disorderly movements in the exchange rate; it should be guided by fundamentals in the medium term. -- Progress on structural reforms (including on the energy sector and on public financial management) should catalyze more donor support and is essential for supporting growth. A possible new ECF arrangement would entrench macroeconomic stability and promote policies to generate sustained GDP growth.